Peran Sistem Informasi dalam Mendukung Kesuksesan Bisnis Digital : Kajian Narrative Literature Review - Achmad Solechan (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
This study aims to analyze the role of information systems in supporting digital business success, particularly among Small and Medium Enterprises (SMEs), using a Narrative Literature Review (NLR) approach. The review examined various national and international scientific articles obtained from Scopus, ScienceDirect, SpringerLink, and Google Scholar databases published between 2021 and 2025. The findings reveal that information systems play a strategic role in improving operational efficiency, decision-making quality, innovation capability, customer engagement, and organizational competitive advantage in the digital transformation era. Technologies such as Enterprise Resource Planning (ERP), Customer Relationship Management (CRM), cloud computing, Artificial Intelligence (AI), and digital platforms have proven to enhance SME performance and business sustainability. In addition to technological factors, the successful implementation of information systems is influenced by organizational readiness, digital capabilities of human resources, organizational culture, transformational leadership, as well as government support and digital infrastructure. The study also identifies several challenges in SME digitalization, including limited digital literacy, technological readiness, and financial resources. This research contributes theoretically by integrating the perspectives of Resource-Based View (RBV), Dynamic Capability Theory, and Digital Transformation Theory in explaining information systems as strategic organizational resources.